Analisis Pengaruh Mekanisme Corporate Governance terhadap Kemungkinan Terjadinya Financial Distress - Bernadin Arum Sekar Budiningsih; Agustinus Tri Kristanto; Gien Agustinawansari (Fakultas Ekonomi, Universitas Sanata Dharma Yogyakarta, 2021)
This study aims to clarify the impact of corporate governance mechanisms on the potential financial distress of manufacturing companies listed on the Indonesia Stock Exchange from 2016 to 2018. The corporate governance mechanisms considered in this study are management ownership, institutional ownership, percentage of independent commissioners, board size, and audit committee financial experts. The sampling method used purposive sampling and the data was taken from 108 samples. The analytical method was performed using logistic regression analysis. The results of this study show that institutional ownership is actively associated with potential financial difficulties. Other corporate governance mechanisms, such as management ownership, percentage of independent committee members, board size, and audit committee financial experts, are known to influence the potential for financial distress. do not have.